2016
DOI: 10.1002/pbc.26225
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for central line-associated bloodstream infection in pediatric oncology patients with a totally implantable venous access port: A cohort study

Abstract: Risk factors for CLABSI in pediatric cancer patients with a TIVAP may be related to the severity of the child's condition at catheter insertion. Insertion of the catheter before chemotherapy and unfavorable conditions such as malnutrition and bone marrow aplasia can increase the risk of CLABSI. Protocols must be revised and surveillance increased over the first 10 weeks of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
40
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 35 publications
8
40
4
Order By: Relevance
“…20 This is also shown in another national study, which presented an ID of 1.2 per 1000 CVC-days in pediatric HSCT patients. 12 Moreover, in our study, the ID of CVC-LC-BSI was 50% higher in patients with a permanent CVC, although this did not reach statistical significance (P = .79). In the study conducted by Besides, Libbrecht et al, 21 in a multivariate analysis, showed that grafts from unrelated donors were found to be an independent risk factor for bacteremia (P = .003).…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…20 This is also shown in another national study, which presented an ID of 1.2 per 1000 CVC-days in pediatric HSCT patients. 12 Moreover, in our study, the ID of CVC-LC-BSI was 50% higher in patients with a permanent CVC, although this did not reach statistical significance (P = .79). In the study conducted by Besides, Libbrecht et al, 21 in a multivariate analysis, showed that grafts from unrelated donors were found to be an independent risk factor for bacteremia (P = .003).…”
Section: Discussioncontrasting
confidence: 72%
“…A national study also showed a similar proportion of GNB (46.8%), but coagulase-negative staphylococci were the most prevalent. 12 In another recent study, in Egypt, including all LC-BSIs not associated with CVCs, gram-positive bacteria were the most commonly encountered, whereas GNB comprised 43% of the isolated microorganisms. 26 The percentage of infections attributed to coagulase-negative staphylococci was also important.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies of CLABSI in children undergoing cancer treatment have identified several risk factors, such as failure to observe hygiene procedures, longer duration of catheterisation, more frequent CVC manipulation, double‐lumen catheters, young age, chronic malnutrition and an absolute neutrophil count of <0.5 × 109/L . However, the varying infection rates that have been reported probably reflect the different methodology used and the differences in patient cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…A central venous access is mandatory for hyperosmolar, basic (pH ≤4.0), alkaline (pH ≥9.0) and local irritant medication, such as chemotherapy, antibiotics and parenteral nutrition. Moreover, high pressure infusions such as those required for computed tomographic examinations of up to 5 ml/s, as well as blood tests, which can be performed through such selected systems, streamlining workflow and increasing patient quality of life (1)(2)(3).…”
mentioning
confidence: 99%